A Dutch-French comparison of dependence, trust and commitment in buyer-supplier relationships: a purchasing portfolio approach. (14th April 2009) - Kibbeling, Mirjam I.; Gelderman, Cees J.; Ulijn, Jan M.; Van Weele, Arjan J.; , Richard Calvi
National culture is likely to affect trust, commitment and dependence in buyer-supplier relationships. Yet, empirical research on buyer-supplier relationships in different cultural settings is still limited. This article presents the findings of an exploratory study into the role of culture in different types of buyer-supplier relationships. Hypotheses have been tested, using data from a survey among 84 French purchasing professionals and data gathered before in the Netherlands with 216 colleagues. A comparative analysis revealed that the cultural background of purchasers does affect their perceptions of trust, commitment and dependence in supplier relationships. French purchasers demonstrate lower levels of (affective) commitment, competence trust and goodwill trust towards their suppliers, compared to their Dutch colleagues. These findings are inconsistent to what French-Dutch intercultural studies suggest. Focus group discussions indicate that Professional Culture might be more important than National Culture for the explanation of differences in buyer-supplier relationships.